The first artists in search of the world's oldest art - Lorblanchet, Michel 1937-; Bahn, Paul G. 1953- (Thames & Hudson, 2017)
Where do we find the world's very first art? When, and why, did people begin experimenting with different materials, forms and colors? Were our once-cousins, the Neanderthals, also capable of creating art? Prehistorians have been asking these questions of our ancestors for decades, but only very recently, with the development of cutting-edge scientific and archaeological techniques, have we been able to piece together the first chapter in the story of art
Keywords: Kunst; Vor- und Frühgeschichte; Art, Prehistoric; Art, Primitive